Leakage Current Monitoring System for High Voltage Insulator using LabVIEW - Ramlan, Muhammad Haziq; Abd. Rahman , Rahisham (Evolution in Electrical and Electronic Engineering, 2023)
This paper describes a leakage current monitoring system designed to analyse the efficacy of high-voltage insulators. Establishing monitoring parameters, constructing a graphical user interface (GUI) based on these parameters, and analysing the monitoring system are the objectives of the study. The system employs the LabVIEW methodology, which provides a customizable and dependable GUI solution. Data acquisition (DAQ) captures and processes pertinent insulator data for accurate monitoring of leakage current. The system is also equipped with overvoltage and overcurrent protection mechanisms. In the FKEE High Voltage Laboratory, the designed leakage current monitoring system is assessed. The system provides effective user input, data visualization, recording, and alerts. The numerical results demonstrate the accuracy and dependability of the system in identifying and measuring leakage current in high-voltage insulators.